In silico analysis of phag-like protein in ralstonia eutropha h16, potentially involved in polyhydroxyalkanoates synthesis (2019)
ABSTRACT : Polyhydroxyalkanoates (PHA) are synthesised by bacteria as carbon storage material. The protein PhaG directs carbon from non-related carbon sources such as glycerol, metabolised through fatty acid de novo synthesis (FAS) pathway, with PHA synthesis. The gene that codifies for this protein has not yet been found in the genome of Ralstonia eutropha H16, a model organism. By bioinformatic comparison to already known PhaG proteins, a PhaG-like protein was found codified by gene H16_A0147 and presence of the gene was preliminary confirmed by PCR. This is the first study that shows the presence and characteristics of a PhaGlike protein in R. eutropha H16 and represents the first step for the identification of a connection between FAS and PHA pathways in this model bacterium. Further gene deletion and enzymatic activity studies are necessary to confirm this potential relationship, which could improve industrial PHA production and utilisation of agroindustrial residues such as glycerol.